Considering Criteria for Active Phase Labor Management of Nulliparous Women: A Cost-Effectiveness Analysis - Schmidt, Eleanor M.; Hersh, Alyssa R.; Tuuli, Methodius; Cahill, Alison G.; Caughey, Aaron B. (American Journal of Perinatology, 2021)
Objective The aim of the study is to evaluate differences in maternal and neonatal outcomes based on updated criteria for defining active labor at 6 cm of cervical dilation and to determine if these recommendations are cost-effective.Study Design A decision-analytic model was built using TreeAge Pro 2020 software. We included maternal outcomes of mode of delivery, endometritis, postpartum hemorrhage requiring transfusion, and death. Neonatal outcomes included rates of shoulder dystocia and permanent brachial plexus injury. Costs and quality-adjusted life years (QALYs) were included from the maternal and infant perspectives. We used a willingness-to-pay threshold of $100,000 per QALY and all model inputs were subjected to sensitivity analysis.Results In a theoretical cohort of 1.4 million women, a threshold of 6 cm to define active labor resulted in 373,668 fewer cesarean deliveries, 33,181 fewer cases of endometritis, 143 fewer postpartum hemorrhages requiring transfusions, and seven fewer maternal deaths when compared with a threshold of 4 cm. However, there were higher rates of adverse neonatal outcomes, including 484 more cases of shoulder dystocia and 17 more instances of permanent brachial plexus injury. Using 6 cm as the threshold resulted in lower costs and greater effectiveness, making it a dominant strategy. Multivariate sensitivity analysis demonstrated the model was robust over a wide range of assumptions.Conclusion In this model, considering 6 cm of cervical dilation as the threshold for the active phase of labor compared with 4 cm was a cost-effective strategy to prevent primary cesarean deliveries, lower costs, and improve maternal outcomes, despite associated increased adverse neonatal outcomes.Key Pointsg
Keywords: active phase; cesarean delivery; cost-effectiveness analysis; labor; labor arrest; obstetric management